Validation of the Persian version of self-care tools for hypertension among older adults - Farideh Barati; Leila Sadeghmoghadam; Moosa Sajjadi; Shima Nazari; Narjes Bahri (Medicinski glasnik, 2019)
Aim: To validate two sub-scales of self-care behaviour and self-efficacy of hypertension in elderly patients in Iran using an English scale developed by Dr. Han et al. Methods: The Persian version of two sub-scales of self-care behavior and self-efficacy was validated for 300 elderly people who suffered from hypertension. These sub-scales were translated into Persian according to the Wild et al. model. The validity of the tool was confirmed through formal, content and structural validity and reliability through calculation of internal consistency and time stability. Results: Cronbach's alpha was reported to 0.85 for behavior, 0.86 for self-efficacy. Pearson's correlation coefficient for behavior was 0.89, for self-efficacy 0.92. Intraclass correlation coefficient (ICC) was 0.84 for behavior and 0.88 for self-efficacy. The minimum acceptable content validity ratio (CVR) for each grade was equal to 49.0 and for the content validity index (CVI) equal to 0.79, indicating that all items obtained the grade points. In exploratory analysis, two dimensions of diet and disease management were determined for both sub-scales, which were approved according to fit indicators. Conclusion: The Persian version of the Self-Care Tools for hypertension showed favourable validity and reliability, and thus it can be used for measuring the level of self-care for hypertension in Iranian elderly population.
Keywords: aged; hypertension; Persian; self-care; validation